Eight new species of Gulella Pfeiffer, 1856 from the south-east coast of South Africa (Gastropoda: Streptaxidae) - Cole, Mary; Herbert, David (European Journal of Taxonomy, 2022)
Eight new species of Gulella Pfeiffer, 1856 are described from south-eastern South Africa, occurring over a linear distance of 550 km within the Maputaland-Pondoland-Albany biodiversity hotspot. Seven species are narrow-range endemics, while Gulella kenbrowni sp. nov. occurs somewhat patchily over most of this distance. The very similar G. fordycei sp. nov. is recorded from only one small nature reserve in medium-altitude mistbelt forest. Six species, G. crookesi sp. nov., G. maraisi sp. nov., G. mkombeni sp. nov., G. abbotti sp. nov., G. donaikeni sp. nov. and G. calcicola sp. nov. each occur at one or a few isolated localities along a narrow strip of 140 km at or near the coast. The latter two are found only in the Marble Delta region, where mining has badly degraded and continues to threaten their habitat, and appear to meet the criteria for Red-Listing as Critically Endangered. Six species occur in nature reserves, highlighting the importance of small pockets of protected habitat for the conservation of terrestrial snails.